Dentate Granule Cells Are Hyperexcitable in the TgF344-AD Rat Model of Alzheimer's Disease - Smith, Lindsey A.; Goodman, Anthoni M.; McMahon, Lori L. (Frontiers in Synaptic Neuroscience, 2022)
The dentate gyrus is both a critical gatekeeper for hippocampal signal processing and one of the first regions to dysfunction in Alzheimer’s disease (AD). Accordingly, the appropriate balance of excitation and inhibition through the dentate is a compelling target for mechanistic investigation and therapeutic intervention in early AD. Previously, we reported increased LTP magnitude at medial perforant path-dentate granule cell (MPP-DGC) synapses in slices from both male and acutely ovariectomized female TgF344-AD rats compared to Wt as early as 6 months of age that is accompanied by an increase in steady-state postsynaptic depolarization during the high-frequency stimulation used to induce plasticity. Subsequently we found that heightened function of β adrenergic receptors (-ARs) drives the increase in LTP magnitude, but the increase in steady-state depolarization was only partially due to -AR activation. Because we previously reported no detectable difference in spine density or presynaptic release probability, we entertained the possibility that dentate granule cells (DGCs) themselves might have modified passive or active membrane properties which may contribute to the significant increase in charge transfer during high-frequency stimulation. Using brain slice electrophysiology from 6 month old acutely ovariectomized female rats, we found significant changes in passive membrane properties and active membrane properties leading to increased DGC excitability in TgF344-AD rats. Specifically, TgF344-AD DGCs have an increased input resistance and decreased rheobase, decreased sag, and increased action potential (AP) spike accommodation. Importantly, we find that for the same amount of depolarizing current injection, DGCs from TgF344-AD compared to Wt rats have a larger magnitude voltage response which was accompanied by a decreased delay to fire the first action potential, indicating TgF344-AD DGCs membranes are more excitable. Taken together, DGCs in TgF344-AD rats are more excitable, which likely contributes to the heightened depolarization during high frequency synaptic activation.